Biosynthesis of novel metallic silvers on kraft papers using cephalotaxus harringtonia fruit extract as a sustainable stabilizing agent (KP@AgNP) - Wei, Shaofeng; Liu, Xiaoyi; Xie, Jiao; Liu, Huijuan; Zeng, Qibing; wang, Guoze; Luo, Peng (Frontiers in Bioengineering and Biotechnology, 2022)
Greenly synthesized silver nanoparticles (AgNPs) on different cellulosic materials show tremendous potential for colorful, biocidal, and reasonably strong products by replacing the traditional chemical-based synthesis protocols. This study reports on a novel in situ synthesis protocol for synthesizing green and sustainable AgNPs over cellulosic kraft paper substrates using a bio-based stabilizing agent (Cephalotaxus harringtonia fruit extract). The protocol could play a significant role in packaging industries. The aqueous extracts of Cephalotaxus harringtonia fruits have been used to synthesize the metallic silver. The deposited AgNPs values were investigated through XRF (X-ray fluorescence) analysis. The number of deposited nanoparticles (NPs) was 268 ± 7, 805 ± 14, and 1045 ± 16 PPM, respectively for 0.5, 1.5, and 2.5 mM silver precursors. The developed products were tested with SEM (scanning electron microscopy), SEM-mediated elemental mapping, EDX (energy disruptive X-ray), FTIR (Fourier transform infrared spectroscopy), and XRD (X-Ray diffraction). XRD analysis further confirmed the presence of peaks for elemental AgNP on the deposited papers. Colorimetric values were measured to confirm the colorful appearances of the developed metallic silvers. Mechanical properties were tested in terms of the tensile index and bursting index. Moreover, the statistical analysis of coefficient of variations (R2) and a post-hoc ANOVA test that adopted the Newman-Keul methodology also confirm the significance of developed nanoparticles in the papers. The shielding capacity against UV light was also investigated; all the AgNPs-treated products provided values higher than 40, demonstrating the strong UV resistance capability of the kraft paper material. Overall, the study confirms a successful development of green AgNPs on paper materials.